Another Year, Another Methodology: Are Rankings Telling Us Anything New? - Hazelkorn, Ellen; Gibson, Andrew (International Higher Education, 2016)
Each year brings new rankings, and new changes to how they purport to measure quality. This article looks at recent changes in the main global rankings, and asks whether these annual methodological tweaks actually tell us anything new about higher education.